Synthesis and Application of a Spirocompound as Clean Viscosity-Reducer for Crude Oil. (1st March 2016) - Chen, Shijun; Zhao, Kang; Chen, Gang; Bai, Li; Feng, Lajun
Abstract : Heavy oil transportation has become a highly technical operation facing complex difficulties. One of the major difficulties in the pipeline transportation is the high viscosity that requires efficient and economical ways to deal with. The typical polymer viscosity reducers are a negative problem during oil refinement process for their chemical properties. The objective of this study is to seek small molecular compound, different from the traditional polymers, to reduce the viscosity of the crude oil. In this work, a spirocompound, 3, 9-diphenyl-2, 4, 8, 10-tetraoxa-spiro[5.5 ]undecane, was synthesized catalyzed by zeolite and modified zeolite, and the product was fully characterized by NMR, MS, and TG. Then, it was used as viscosity reducer for crude oil. The factors such as dosage and temperature on the viscosity behavior have been studied. The results showed a significant viscosity reduction at different temperature, and the most economical dosage is 500 ppm. The multiphenyl groups can interact with asphaltene byπ - π stacking, and the spirostructure can fix the stacking in different direction, which can prevent the agglomeration of wax crystals.